2016
DOI: 10.1016/j.ajhg.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in CDC14A , Encoding a Protein Phosphatase Involved in Hair Cell Ciliogenesis, Cause Autosomal-Recessive Severe to Profound Deafness

Abstract: By genetic linkage analysis in a large consanguineous Iranian family with eleven individuals affected by severe to profound congenital deafness, we were able to define a 2.8 Mb critical interval (at chromosome 1p21.2-1p21.1) for an autosomal-recessive nonsyndromic deafness locus (DFNB). Whole-exome sequencing allowed us to identify a CDC14A biallelic nonsense mutation, c.1126C>T (p.Arg376(∗)), which was present in the eight clinically affected individuals still alive. Subsequent screening of 115 unrelated indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Recently, it has been shown that mutations in two kinociliary proteins, Cdc14a and Dcdc2, are associated with human recessive deafness (Delmaghani et al, 2016;Grati et al, 2015). Zebrafish morphants (MOs) for dcdc2 and cdc14a showed kinocilium abnormalities with the concomitant defects in hair cell morphology and function, reinforcing the notion of a direct involvement of primary cilia in hair cell function (Delmaghani et al, 2016;Grati et al, 2015).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Recently, it has been shown that mutations in two kinociliary proteins, Cdc14a and Dcdc2, are associated with human recessive deafness (Delmaghani et al, 2016;Grati et al, 2015). Zebrafish morphants (MOs) for dcdc2 and cdc14a showed kinocilium abnormalities with the concomitant defects in hair cell morphology and function, reinforcing the notion of a direct involvement of primary cilia in hair cell function (Delmaghani et al, 2016;Grati et al, 2015).…”
Section: Introductionmentioning
confidence: 86%
“…In vertebrates, primary cilia are implicated in several developmental pathways and act as signaling centers mediating intercellular communications (Ezratty et al, 2011;Breunig et al, 2008;Delling et al, 2016). Dysfunction of cilia, due to mutations in ciliary proteins or proteins involved in vesicular transport, is associated with a broad spectrum of human disorders that affect sensory neuron physiology (hearing/balance, olfaction and vision), as well as organ development and function (Delmaghani et al, 2016;Grati et al, 2015;Jagger et al, 2011;Rachel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human CERKL mutations are associated with retinitis pigmentosa, a known ciliopathy (Tuson et al, 2004), but the mechanism of CERKL action is poorly defined; we founbd that Cerkl localized to axonemes, suggesting a novel avenue of inquiry. Likewise, Rfx transcription factors are linked to hearing loss (Elkon et al, 2015), and we identified three proteins with cilia and/or basal body localization that are encoded by genes that are known to be involved in human deafness (Elmod3, Lrtomta, Cdc14a) (Ahmed et al, 2008;Delmaghani et al, 2016;Jaworek et al, 2013).…”
Section: Localization Of Proteins Implicated In Human Diseasementioning
confidence: 99%
“…Approximately 120 genes responsible for non-syndromic HL have been identified so far [1,2]. Since 2016, the gene CDC14A (OMIM: *603504, ENSG00000079335) has been associated with autosomal recessive non-syndromic deafness-32 (DFNB32, OMIM: #608653) [3]. Two years later, it was recognized as causing hearing impairment and infertile male syndrome (HIIMS) [4].…”
Section: Introductionmentioning
confidence: 99%